Factors associated with persistent poorly controlled diabetes mellitus: Clues to improving management in patients with resistant poor control. (December 2014) - Crowley, Matthew J; Holleman, Rob; Klamerus, Mandi L; Bosworth, Hayden B; Edelman, David; Heisler, Michele
Objectives: Patients with persistent poorly controlled diabetes mellitus (PPDM), defined as an uninterrupted hemoglobin A1c >8.0% for ≥1 year despite standard care, are at high risk for complications. Additional research to define patient factors associated with PPDM could suggest barriers to improvement in this group and inform the development of targeted strategies to address these patients' resistant diabetes. Methods: We analyzed patients with type 2 diabetes from a multi-site randomized trial. We characterized patients with PPDM relative to other patients using detailed survey data and multivariable modeling. Results: Of 963 patients, 118 (12%) had PPDM, 265 (28%) were intermittently poorly controlled, and 580 (60%) were well-controlled. Patients with PPDM had younger age, earlier diabetes diagnosis, insulin use, higher antihypertensive burden, higher low-density lipoprotein cholesterol, and lower statin use relative to well-controlled patients. Among patients with objective adherence data (Veterans Affairs patients), a larger oral diabetes medication refill gap was associated with PPDM. Discussion: Strategies are needed to target-specific barriers to improvement among patients whose diabetes is resistant to standard diabetes care. Our data suggest that strategies for targeting PPDM should accommodate younger patients' lifestyles, include medication management for insulin titration and comorbid disease conditions, and address barriers to self-management adherence.